1978
DOI: 10.1073/pnas.75.12.6324
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cholecystokinin-like immunoreactivity in isolated nerve terminals.

Abstract: Subcellular fractionation of the rat cerebral cortex demonstrated the presence of immunoreactive cholecystokinin in the pellet identified by electron microscopy as containing a high proportion of synaptic vesicles. The recovery in this pellet of 40% of the total immunoreactivity in the initial cortical extract is quite comparable to the recovery of other peptides such as vasoactive intestinal polypeptide and somatostatin, which are also located in synaptosomes and for which roles as neuroregulators or transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The origin of the released CCK-LI is most probably neuronal since CCK-LI has been reported to be concentrated in CNS nerve terminals (Pinget et al, 1978). Possible 'gliasomal' contamination of our nerve ending preparations should not contribute significantly to the released peptide inasmuch as CCK has not been detected in glial cells (Loren et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the released CCK-LI is most probably neuronal since CCK-LI has been reported to be concentrated in CNS nerve terminals (Pinget et al, 1978). Possible 'gliasomal' contamination of our nerve ending preparations should not contribute significantly to the released peptide inasmuch as CCK has not been detected in glial cells (Loren et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chronic undernutrition in early life was examined by placing newborn rats in artificially enlarged litters of 22 pups each. Animals reared in this manner suffer significant early malnutrition and remain stunted as adults (12)(13)(14).…”
Section: Methodsmentioning
confidence: 99%
“…Of the several different fragments of CCK, the octapeptide (CCK-8) is believed to be the predominant form in the brain (Rehfeld, 1978;Larsson & Rehfeld, 1979). CCK-8 has been found in cell bodies, neurones and nerve terminals (Pinget et al, 1978;Innis et al, 1979;Vanderhaeghen et al, 1980), and specific CCK-receptors have been demonstrated in discrete areas of the brain (Zarbin et al, 1983;Van Dijk et al, 1984;Day et al, 1986) including a number of regions that are considered to be involved 'Author for correspondence. in the regulation of feeding behaviour.…”
Section: Introductionmentioning
confidence: 99%